2010
DOI: 10.1158/0008-5472.can-09-3642
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine Receptor CXCR7 Is Highly Expressed in Human Glioma Cells and Mediates Antiapoptotic Effects

Abstract: The chemokine CXCL12/stromal cell-derived factor-1 and its receptor CXCR4 play a major role in tumor invasion, proliferation, and metastasis. Recently, CXCR7 was identified as a novel, alternate receptor for CXCL12 and CXCL11/I-TAC. Because both chemokines are expressed abundantly in human astrocytomas and glioblastomas, we investigated the occurrence and function of both receptors in astroglial tumors. In situ, CXCR7 is highly expressed on tumor endothelial, microglial, and glioma cells whereas CXCR4 has a mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
284
0
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 251 publications
(307 citation statements)
references
References 34 publications
15
284
0
8
Order By: Relevance
“…It has previously been reported by Hattermann et al that both CXCR4 and CXCR7 are expressed in astrocytomas/glioblastomas but CXCR4 is found on stemlike cells whereas CXCR7 detected on tumor-infiltrating microglial cells. They concluded that CXCR4 is likely to contribute to the recruitment of tumor stem like cells while CXCR7 seems to inhibit the apoptosis of glioma cells (Hattermann et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported by Hattermann et al that both CXCR4 and CXCR7 are expressed in astrocytomas/glioblastomas but CXCR4 is found on stemlike cells whereas CXCR7 detected on tumor-infiltrating microglial cells. They concluded that CXCR4 is likely to contribute to the recruitment of tumor stem like cells while CXCR7 seems to inhibit the apoptosis of glioma cells (Hattermann et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The human glioma cell lines, U343 and A764, were propagated in 90% DMEM (Lonzan) and 10% fetal calf serum (FCS; Hattermann et al, 2010). Primary astrocytic cultures and glioma cell cultures were switched to serum-free N2-medium 24 h and 6 h before experiments, respectively, and additionally treated with the following substances as specified in the text: SDF-1a (Millipore, Billerica, MA), I-TAC (Biozol, Eching, Germany); FGF-2 (Peprotech, Rocky Hill, NJ); AMD3100 (dissolved in water; Sigma-Aldrich, St. Louis, MO), CCX771 (dissolved in DMSO; ChemoCentryx, Mountain View, CA), U73122, U73343 (both Merck, Darmstadt, Germany), PTX (Merck).…”
Section: Materials and Methods Cell Culturesmentioning
confidence: 99%
“…CXCR7 expression increases in human astrocytoma tissue and is largely confined to GFAP-expressing cells (Hattermann et al, 2010). Likewise, several human astroglioma cell lines express detectable levels of CXCR7, but not of CXCR4 (Hattermann et al, 2010).…”
Section: Sdf-1-bound Cxcr7 Activates G I/o Proteins In Human Astrocytmentioning
confidence: 99%
See 2 more Smart Citations